Kinematic fitting of neutral current events in deep inelastic ep collisions. (27th September 2022) - Aggarwal, Ritu; Caldwell, Allen
Abstract: In this paper we present a technique to reconstruct the scaling variables defining ep deep inelastic scattering by performing a kinematic fit. This reconstruction technique makes use of the full potential of the data collected. It is based on Bayes' Theorem and involves the use of informative priors. The kinematic fit method has been tested using a simulated sample of ep neutral current events at a center of mass energy of 318 GeV with Q 2 > 400 GeV 2 . In addition to the scaling variables, this method is able to estimate the energy of possible initial state radiation ( Eγ ) which otherwise goes undetected. A better resolution than standard electron and double angle techniques in the reconstruction of scaling variables is achieved using a kinematic fit.